Radical prescription : citizenship and the politics of tuberculosis in twentieth-century Cuba - Urban, Kelly (The University of North Carolina Press, 2023)
"In this first comprehensive study of tuberculosis in modern Cuba, Kelly Urban analyzes the medical, social, and governmental responses to the highly contagious disease, particularly as the island was heading into and emerging from the 1959 revolution. Tuberculosis--one of the top three causes of death in Cuba at the beginning of the twentieth century--provides a window onto broad questions of citizens' rights, biomedicine and public health, and political change"-- Provided by publisher.
Keywords: Tuberculosis -- Cuba -- History -- 20th century.; Public health -- Cuba -- History -- 20th century.; Medical policy -- Cuba -- History -- 20th century.; Cuba -- History -- 1895-; Cuba -- Politics and government -- 1895-; Tuberculose -- Cuba -- Histoire -- 20e siècle.; Santé publique -- Cuba -- Histoire -- 20e siècle.; Politique sanitaire -- Cuba -- Histoire -- 20e siècle.; Cuba -- Histoire -- 1895-; Cuba -- Politique et gouvernement -- 1895-; SOCIAL SCIENCE / Ethnic Studies / Caribbean & Latin American Studies; Tuberculosis; Public health; Politics and government; Medical policy; Cuba; Social services & welfare, criminology.; Health and Wellbeing.; Since 1895; History